Visualization of solute diffusion into cell walls in solution-impregnated wood under varying relative humidity using time-of-flight secondary ion mass spectrometry - Peiming Zheng (Nature Portfolio, 2018)
Abstract The purpose of the present study is to clarify the diffusion of non-volatile substances into cell walls during the conditioning procedure under varying relative humidities (RH). In this paper, wood blocks were impregnated using an aqueous solution of melamine formaldehyde (MF), and they were subsequently conditioned under RHs of 11, 43, and 75%. The solute that diffused into the cell walls was visualized using time-of-flight secondary ion mass spectrometry (TOF-SIMS). The volumetric relative swelling of the samples during the conditioning procedure was calculated. The results showed increased cell wall swelling at higher RH, which may have been caused by higher MF diffusion into the cell walls and/or higher moisture content. Cryo-TOF-SIMS measurements showed that more cell cavities were unfilled with MF at higher RH, indicating that most of the MF diffused from the cell cavities into the cell walls. The relative intensity of MF in the cell walls of the cured samples was evaluated from dry-TOF-SIMS images, which showed a higher relative intensity of MF in the cell walls at higher RH. With the ability to visualize and semi-quantitatively evaluate the solute in cell walls, TOF-SIMS will serve as a powerful tool for future studies of solute diffusion mechanisms in solution-impregnated wood.